2018
DOI: 10.1002/cbin.11002
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of exosomal miR‐106b‐5p derived from cholesteatoma perimatrix fibroblasts promotes angiogenesis in endothelial cells by overexpression of Angiopoietin 2

Abstract: Human cholesteatoma perimatrix fibroblasts (hCPFs) can stimulate the endothelial cells of nearby microvessels to proliferate and migrate in a paracrine manner. Exosomes, secreted from various cell types, are one of the most important paracrine factors and play critical roles in intercellular communication. However, whether exosomes derived from human cholesteatoma perimatrix fibroblasts (hCPFs-Exo) can promote angiogenesis has not been reported. In this study, we isolated exosomes secreted by hCPFs and observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Another in vitro study showed that human cholesteatoma perimatrix fibroblast-derived sEVs promote angiogenesis through downregulation of miR-106b-5p in sEVs, leading to the overexpression of Angiopoietin-2 in human umbilical vein endothelial cells (HUVECs). Furthermore, sEVs contributed to enhanced tube formation and cell migration [49]. These findings posit sEVs as important factors in the pathogenesis and progression of OME and chronic otitis media with cholesteatoma.…”
Section: Sevs and Airway Epitheliummentioning
confidence: 72%
“…Another in vitro study showed that human cholesteatoma perimatrix fibroblast-derived sEVs promote angiogenesis through downregulation of miR-106b-5p in sEVs, leading to the overexpression of Angiopoietin-2 in human umbilical vein endothelial cells (HUVECs). Furthermore, sEVs contributed to enhanced tube formation and cell migration [49]. These findings posit sEVs as important factors in the pathogenesis and progression of OME and chronic otitis media with cholesteatoma.…”
Section: Sevs and Airway Epitheliummentioning
confidence: 72%
“…miR-106b-5p targets cTSA to suppress the invasion and metastasis of colorectal cancer (31), but miR-106b-5p promotes stem cell-like properties of hepatocellular carcinoma cells through targeting PTEN via a PI3K/Akt signaling pathway (32). Li et al (20) demonstrated that miR-106b-5p binds the 3'-UTR of Angpt2 to induce migration and tube formation of HUVEcs, and hcPFs-exosome transport to endothelial cells expressing relatively low amounts of miR-106b-5p, promoting angiogenesis through upregulation of Angpt2 (20). miR-106b-5p is pivotal in regulating cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (20) demonstrated that miR-106b-5p binds to the 3'-UTR of Angiopoietin 2 (Angpt2) to induce migration and tube formation of HUVEcs, and human cholesteatoma perimatrix fibroblasts (hCPFs)-exosomes transports miR-106b-5p to endothelial cells and promotes angiogenesis by upregulating expression of Angpt2 (20). miR-106b-5p is pivotal in regulating cell proliferation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al showed that exosomes could promote the ECs angiogenesis induced by oxygen-glucose deprivation via miR-181b-5p/TRPM7 axis [37]. On the contrary, it had been proven that up-regulation of exosomal miR-106b-5p suppressed angiogenesis in ECs by overexpression of angiopoietin 2 [38]. Besides, it had been indicated that exosomes exerted an anti-angiogenic function through transfer of miR-320 into ECs [39].…”
Section: Exosomal Mirnas and Ecs Functionsmentioning
confidence: 99%